2018
DOI: 10.1021/acsami.8b16717
|View full text |Cite
|
Sign up to set email alerts
|

Chalcopyrite ZnSnSb2: A Promising Thermoelectric Material

Abstract: Ternary compounds with a tetragonal chalcopyrite structure, such as CuGaTe 2 , are promising thermoelectric (TE) materials. It has been demonstrated in various chalcopyrite systems, including compounds with quaternary chalcopyrite-like structures, that the lattice parameter ratio, c/a, being exactly 2.00 to have a pseudocubic structure is key to increase the degeneracy at the valence band edge and ultimately achieve high TE performance. Considering the fact that ZnSnSb 2 with a chalcopyrite structure is report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…Despite the high PFs, pnictides are comparable with the chalcogenide counterparts in ZT max because of the cancellation from enhanced κ e s and κ L s. In Figure c, 12 compounds with ZT > 0.6 are labeled. CuInTe 2 and AgGaTe 2 have been experimentally confirmed to be high-performance p-type TE materials, and their experiment ZT values at 700 K are 0.59 and 0.5, respectively, which are consistent with our theoretical results (0.66 and 0.67). , Nomura et al recently reported that ZnSnSb 2 is a promising TE material . The other compounds, predicted TE materials CdSnSb 2 , AgInS 2 , AgGaSe 2 , ZnCdTe 2 , and LiInTe 2 , have been little studied in this context experimentally, but based on the results above, they are promising TE materials.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Despite the high PFs, pnictides are comparable with the chalcogenide counterparts in ZT max because of the cancellation from enhanced κ e s and κ L s. In Figure c, 12 compounds with ZT > 0.6 are labeled. CuInTe 2 and AgGaTe 2 have been experimentally confirmed to be high-performance p-type TE materials, and their experiment ZT values at 700 K are 0.59 and 0.5, respectively, which are consistent with our theoretical results (0.66 and 0.67). , Nomura et al recently reported that ZnSnSb 2 is a promising TE material . The other compounds, predicted TE materials CdSnSb 2 , AgInS 2 , AgGaSe 2 , ZnCdTe 2 , and LiInTe 2 , have been little studied in this context experimentally, but based on the results above, they are promising TE materials.…”
Section: Resultssupporting
confidence: 89%
“…17,19 Nomura et al recently reported that ZnSnSb 2 is a promising TE material. 32 The other compounds, predicted TE materials CdSnSb 2 , AgInS 2 , AgGaSe 2 , ZnCdTe 2 , and LiInTe 2 , have been little studied in this context experimentally, but based on the results above, they are promising TE materials. By the same method, the predicted maximum ZT values of n-type ABX 2 compounds at 700 K are shown in Figure 4d, and 12 compounds with ZT > 0.6 are labeled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the semiconductor, S , σ, and κ e are always coupled with each other, and lattice thermal conductivity κ L is the relatively independent parameter and is affected by the phonon scattering efficiency. The majority strategies to improve the ZT are not only to improve the thermoelectric power factor ( S 2 σ) through carrier concentration optimization, band structure engineering, and energy filtering effect but also to lower the κ L by alloying, introducing alloying, dislocations, nanostructure, low dimensions, strong anharmonicity, and low sound speed to suppress the phonon propagation. Point defect scattering is the most effective and simplest way to reduce κ L in the thermoelectric materials, including vacancy, substitutional, and interstitial defects.…”
Section: Introductionmentioning
confidence: 99%
“…The impurity phase Zn 4 Sb 3 is a well-known p-type thermoelectric phase, [15,16] while ZnSnSb 2 has only a small window of stability. [17] The two different liquid phases that appear in the 400 °C phase diagram transform primarily into crystalline Sn and SnSb when quenched to room temperature.…”
Section: Phase Identificationmentioning
confidence: 99%